Between Income and Material Deprivation in the UK: In Search of Conversion Factors. Issue 1 (2nd January 2016) - Hick, Rod
Abstract: The claim that there are "conversion factors" between people's resources and their capabilities is fundamental to motivating the capability approach, yet is empirically relatively under-examined. The few analyses which exist focus typically on one group—disabled people—and focus overwhelmingly on current income as the relevant measure of resources. This article extends existing analysis on both fronts, analysing conversion factors for a broader range of groups than are typically considered and estimating conversion factors using both a current and five-year average measure of income. It is found that conversion factors based on a five-year average of current income are 40–45% lower than those based on current income. However, a conversion-adjusted income measure, whether based on current or five-year average income, still does not reflect "command over capabilities" because conversion factors are estimated on the basis of group averages, while needs vary for different groups and different households. The article concludes that understanding more clearly the nature of the conversion between resources and functionings or refined functionings represents an important task for those working with the capability approach.